Signal change in hippocampus and current source of spikes in Panayiotopoulos syndrome - Jung Sook Yeom; Youngsoo Kim; Ji Sook Park; Ji Hyun Seo; Eun Sil Park; Jae Young Lim; Chan-Hoo Park; Hyang Ok Woo; Hee-Shang Youn; Oh-Young Kwon (Korean Pediatric Society, 2012)
A 4-year-old girl with Panayiotopoulos syndrome presented with a history of 4 prolonged autonomic seizures. The clinical features of her seizures included, in order of occurrence, blank staring, pallor, vomiting, hemi-clonic movement on the right side, and unresponsiveness. A brain magnetic resonance imaging (MRI) showed a slightly high T2 signal in the left hippocampus. Interictal electoencephalogram revealed spikes in the occipital area of the left hemisphere. We analyzed the current-source distribution of the spikes to examine the relationship between the current source and the high T2 signal. The current source of the occipital spikes was not only distributed in the occipital area of both cerebral hemispheres, but also extended to the posterior temporal area of the left hemisphere. These findings suggest that the left temporal lobe may be one of the hyperexcitable areas and form part of the epileptogenic area in this patient. We hypothesized that the high T2 signal in the left hippocampus of our patient may not have been an incidental lesion, but instead may be related to the underlying electroclinical diagnosis of Panayiotopoulos syndrome, and particularly seizure. This notion is important because an abnormal T2 signal in the hippocampus may represent an acute stage of hippocampal injury, although there is no previous report of hippocampal pathology in Panayiotopoulos syndrome. Therefore, long-term observation and serial follow-up MRIs may be needed to confirm the clinical significance of the T2 signal change in the hippocampus of this patient.